Analisis Usaha Tani Durian (Durio Zibethinus Murr.) Varietas Bido Di Desa Panglungan Kecamatan Wonosalam Kabupaten Jombang - Nur Salam; Handi Widyanto; Arrow S Sakti Darren Leksono (Fakultas Pertanian, Universitas Darul Ulum, 2026)
This study aims to analyze durian farming, specifically the superior local variety Bido, in Panglungan Village, Wonosalam District, Jombang Regency (pp. 1, 6). This area is one of the largest durian production centers in East Java (p. 27). The sampling method was random sampling with a total of 40 durian farmers as respondents (pp. 23, 43). Data analysis used multiple linear regression to examine the influence of production factors simultaneously and partially, and income analysis to determine the economic value of the Bido variety (pp. 24-25). The F-test results showed that land area, seeds, fertilizer, and pesticide variables simultaneously had a significant effect on durian production (F count 6.352 > F table 2.61) (p. 30). Partially, only the seed variable had a significant effect on production yield (p. 31). Based on a financial analysis of the Bido variety, the accumulated managed land area of ​​38,500 m² with a total of 1,005 trees yielded a harvest of 1,455 fruits and recorded a total income of Rp 5,837,000,000 (pp. 34-35). This income is proven to be superior when compared to other local varieties such as Merica and Obet (pp. 22, 36, 38).